Best Practices Guide for Centrifugal Pump Maintenance: Panduan Praktik Terbaik Pemeliharaan Pompa Sentrifugal - Yahya, Wahyu Hikmatiarun; Mulyadi, Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the efficiency of centrifugal pumps, which enhance fluid movement by converting kinetic to dynamic potential energy via an impeller. Maintenance strategies—regular, predictive, and preventive—are analyzed for their impact on pump longevity and reliability. Results demonstrate that effective maintenance reduces operational costs and extends pump life, suggesting significant performance improvements across industrial applications. Highlight : Effective maintenance boosts pump longevity and reliability. Regular, predictive, and preventive maintenance methods analyzed. Significant performance improvements achievable with proper maintenance. Keywords: Centrifugal pumps, Maintenance strategies, Pump efficiency, Operational costs, Industrial applications